Mbili-Mbili technology: Increasing legume production in East Africa - Kihara, Job Maguta; Kinyua, Michael Wanjohi (2022)
Mbili-Mbili is a cereal-legume intercropping strategy involving three crops with different growth patterns spatially configured within a field. It was developed within the Africa Research in Sustainable Intensification for the Next Generation (Africa RISING) Program to get smallholder households out of hunger, food insecurity, malnutrition and poverty. Previously, significant work has been done to develop practices such as integrated soil fertility management (ISFM) that increase maize (Zea mays) productivity with success. However, legume productivity remains low, e.g., < 250 kg/ha for beans (Phaseolus vulgaris) and < 400 kg/ha for pigeon pea (Cajanus cajan). Recognizing this, the International Center for Tropical Agriculture (CIAT), a partner in the Africa RISING Program, developed and validated legume-based interventions in Babati, Tanzania, amongst which was Mbili-Mbili.